Implementasi Tenggang Waktu Pengajuan Perceraian Menurut Surat Edaran Mahkamah Agung Nomor 1 Tahun 2022 Di Indonesia - Pasaribu, Medina Ratu Rahma; Siregar, Muhammad Yusuf; Tampubolon, Wahyu Simon (Universitas Semarang, 2024)
This research aims to examine the reasons the Panel of Judges granted divorce in the Rantau Prapat Religious Court Decision No.1473/PDT.G/2023/PA.RAP. SEMA (Supreme Court Circular Letter) is a circular from the leadership of the Supreme Court for the judiciary containing education on the implementation of justice in a more administrative manner. PP (Government Regulation) Number 9 of 1975 does not explain the time for a dispute before the court recognizes the reason for divorce.. In this case, the Plaintiff filed a lawsuit for divorce on the grounds that continuous disputes, (domestic violence) domestic violence and the defendant using drugs. The Plaintiff and Defendant have not lived apart for six months, but in SEMA Number 1 of 2022 there is a provision that divorce on the grounds of continuous disputes and quarrels can be granted if it is proven that the husband and wife have had continuous disputes and quarrels or have lived apart for at least six months. The panel of judges granted the lawsuit because they had not lived apart for six months, so further study was needed regarding the reasons for granting the lawsuit. The research uses normative juridical methods by exploring theories, concepts and legislation related to this research. The results of the research showed that the Panel of Judges granted divorce cases that had not reached the minimum requirement of being separated for six months if conditions in the household did not allow it to continue because it could be dangerous. In this case, considering the sake of justice and the aim of the law, namely maintaining the honor or safety of oneself and life, the provisions in SEMA Number 1 of 2022 can be set aside.Penelitian ini bertujuan untuk mengkaji alasan Majelis Hakim mengabulkan perceraian pada Putusan Pengadilan Agama Rantau Prapat No.1473/PDT.G/2023/PA.RAP. SEMA (Surat Edaran Mahkamah Agung) yaitu edaran pimpinan Mahkamah Agung untuk peradilan berisi edukasi pelaksanaan peradilan yang lebih administratif. PP (Peraturan Pemerintah) Nomor 9 Tahun 1975 tidak menjelaskan waktu perselisihan sebelum pengadilan mengakui alasan perceraian. Dalam perkara ini, Penggugat mengajukan gugatan perceraian dengan alasan perselisihan terus menerus, (KDRT) Kekerasan Dalam Rumah Tangga dan Tergugat menggunakan Narkoba. Penggugat dan Tergugat belum enam bulan pisah tempat tinggal, namun dalam SEMA Nomor 1 Tahun 2022 terdapat ketentuan perceraian dengan alasan perselisihan dan pertengkaran terus menerus dapat dikabulkan apabila terbukti suami istri berselisih dan bertengkar terus menerus atau telah berpisah tempat tinggal selama minimal enam bulan. Majelis hakim mengabulkan gugatan dimana mereka belum sampai enam bulan pisah tempat tinggal sehingga perlu adanya kajian lebih jauh mengenai alasan dikabulkannya gugatan. Penelitian menggunakan metode yuridis normatif dengan cara mendalami teori, konsep, perundang-undangan yang berhubungan dengan penelitian ini. Hasil penelitian menunjukkan bahwa Majelis Hakim mengabulkan perkara perceraian yang belum sampai unsur minimal pisah rumah selama enam bulan apabila kondisi dalam rumah tangga tersebut tidak memungkinkan untuk dilanjutkan karena dapat membahayakan. Dalam perkara ini, mengingat demi keadilan serta tujuan hukum yaitu memelihara kehormatan atau keselamatan diri maupun jiwa, sehingga ketentuan pada SEMA Nomor 1 Tahun 2022 tersebut dapat dikesampingkan.